2014
DOI: 10.1158/1078-0432.ccr-12-3734
|View full text |Cite
|
Sign up to set email alerts
|

CHFR Promoter Methylation Indicates Poor Prognosis in Stage II Microsatellite Stable Colorectal Cancer

Abstract: Purpose: Data on the prognostic significance of promoter CpG island methylation in colorectal cancer (CRC) are conflicting, possibly due to associations between methylation and other factors affecting survival such as genetic alterations and use of adjuvant therapy. Here, we examine the prognostic impact of promoter methylation in patients with CRC treated with surgery alone in the context of microsatellite instability (MSI), BRAF and KRAS mutations.Experimental Methods: One hundred and seventy-three CRCs were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
2
39
1
Order By: Relevance
“…We have recently reported that concurrent methylation in NEUROG1 and CDKN2A (p16) is associated with higher recurrence in colorectal cancer patients whereas CIMP classification based on the number of methylated markers was not [ 4 ]. Importance of individual gene methylation such as CHFR , MGMT , and SHISA3 has also been shown in other studies [ 6 , 10 , 11 ].…”
Section: Introductionsupporting
confidence: 64%
“…We have recently reported that concurrent methylation in NEUROG1 and CDKN2A (p16) is associated with higher recurrence in colorectal cancer patients whereas CIMP classification based on the number of methylated markers was not [ 4 ]. Importance of individual gene methylation such as CHFR , MGMT , and SHISA3 has also been shown in other studies [ 6 , 10 , 11 ].…”
Section: Introductionsupporting
confidence: 64%
“…Pelosof et al (18) suggested therefore that docetaxel should be used for the treatment of patients with colorectal cancer who presented with CHFR promoter methylation. Cleven et al (19) reported that hypermethylation of CHFR in patients with colorectal cancer indicates poor prognosis of stage ll colorectal cancer. Subsequently, CHFR methylation may serve for selecting chemotherapy agents for cancers of the digestive tract system, and could be considered a putative prognostic indicator in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the promoter regions of the cysteine dioxygenase 1 (CDO1), tachykinin precursor 1 (TAC1) and checkpoint with forkhead and ring finger domains (CHFR) genes has been reported in various types of cancer (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), including colorectal cancer (12,15,19). The risk factors for pancreatic cancer are similar to those for colorectal cancer, and include cigarette smoking and alcohol consumption (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed molecular classification systems will likely improve the stratification and treatment of CRC patients [7, 1518]. In a previous study of the largest cohort of duodenal adenocarcinoma patients to date, we classified tumors into four subtypes based on the combination of CIMP and MLH1 methylation status.…”
Section: Discussionmentioning
confidence: 99%